Take a picture of me, James VanDerZee! - Loney, Andrea J. (Lee & Low Books Inc., 2017)
"A biography of James Van Der Zee, innovative and celebrated African American photographer of the Harlem Renaissance. Includes an afterword, photos, and author's sources"--Publisher.